(untitled) (Iraqi Journal of Medical Sciences, 2017)
Background: von Willebrand disease (VWD) is the most common, genetically, hereditary and clinically heterogeneous bleeding disorder caused by qualitative or quantitative defects in von Willebrand factor (VWF) that leads to imperfect VWF interaction between platelets and injured blood vessel wall which deteriorate primary hemostasis. Objective: To assess the role of collagen binding assay in the classification of VMD. Methods: A cross sectional study was conducted on 52 suspected known patients with VWD with no consideration to their age or gender who attended the National Center of Hematology. They were submitted to von Willebrand factor antigen (VWF:Ag), factor VIII (FVIII), ristocetin co factor assay (VWF:RCo), ristocetin induced platelet aggregation (RIPA), and collagen binding assay (VWF:CB) at the same center. Results: The patients mean age was 14.42 ±1.64 years, median 10 years, and range of 1-40 years. More than half of cases below 10 years with M:F ratio 1:1.26. Two out of 9 cases of subtype I was diagnosed as subtype II, 4 out of 7 cases of subtype II sub classified as subtype2M and the rest 3 cases sub classified as 2A, 11 out of 36 of subtype III diagnosed as 8 cases for subtype I, and 3 cases for subtype II. Conclusion: VWF:CB assay is an important and effective supplementary test, in addition to three test panel FVIII, VWF:Ag, VWF:RCo, and multimere analysis, for sub classification of VWD. VWF:CB assay has a role in reclassified VWD patients with highly variable clinical presentation and laboratory values. Type III VWD is most frequent diagnosed type among symptomatic patients due to high consanguinity rate which detected earlier with severe bleeding tendency. Keywords:Von Willebrand disease, collagen binding assay, VWF:RCo. Citation: Suha K. Jabbar, Subh S. Al-Mudallal, Zeyad A. Shabeeb, Yusra G. Al-Obaidy, Hind S. Al-Mamoori. The role of collagen binding assay in classification of von Willebrand disease. Iraqi JMS. 2017; Vol. 15(2): 175-180. doi: 10.22578/IJMS.15.2.10